Dimensões sociais de ciência e tecnologia: representações sociais de alunos de escolas públicas de um município paulista - Lopes, Gabriela Zauith Leite (2010)
Educational evaluations show that Brazilian students possess low income in diverse discipline, between them sciences. In the daily one of many schools, the scientific knowledge inhabits in didactic books and not its return - what it would taken to the disinterest and the passivity. The scientific education can bring beyond the learning of the concepts, a critical and contrary vision to the positivism education. The transformations of the conceptions of science if had modified the World War II especially after, and, of some had been transferred to the education, in the education of sciences, by means of curricular lines of direction. . The objective of this research is to identify the vision of science of pupils of the average education of two public schools and to analyze its social representations of science and technology. The theoretical referencial used is the social studies of science and the technology and the STS Movement (Science, Technology and Society). The referencial adopted theoreticianmethodology is the Social Representations, which fulfill the function to understand as the knowledge circulates and as science is appropriate for the society. One is about exploratory research of qualitative nature. In the collection of data interviews with questions with 18 pupils of two public schools of the average education of Ribeirão Preto had been carried through. Software ALCESTE 4,5 was used for systematization of the data and posterior qualitative analysis. The program identified 4 classes: 1) Action of the man in the nature; 2) Technology: a treacherous easiness; 3) The two sides of science and 4) Science: research for the health? The results point with respect to construction of a social representation where science and the technology leave of being associates only to its potential of creation and solution of problems, to accumulate of stocks more critical meanings. The citizens of this research associate the benefits of science to the cure of illnesses and the curses to the wars and the interests for the profit. The knowledge shared for the pupils on the impact of science and the technology in the society sample that these are conscientious of the curses that the scientific progress causes in the environment. The proposal of dialogue and the insertion of social dimensions in the education of sciences open way for science are of the laboratories and inside of the Brazilian realitie.